AN ALGEBRA FOR MODELLING THE SIMULTANEITY IN AGENTS' BEHAVIOR IN SPATIALLY EXPLICIT SOCIAL-ENVIRONMENTAL MODELS - Silva, Washington Sena de Franca; Carneiro, Tiago Garcia de Senna (Revista Brasileira de Cartografia, 2017)
Humanity is the major driver of spatial changes resulting from interactions between social and environmental systems. Environmental models usually apply the agent-based modeling paradigm to describe the social aspects of spatial changes. For this reason, these models have incorporated challenges inherent to this paradigm. One of these challenges is how to provide a semantically correct way to describe and simulate the simultaneity in agents' behavior. In this context, this work describes an algebra to the development of spatially explicit agent-based models in a way that the algebra operators implicitly treat the simultaneity in agents' behavior.